2008
DOI: 10.1016/j.envpol.2007.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of microbial activity, soil water content and added copper on the temporal distribution patterns of HCB and DDT among different soil organic matter fractions

Abstract: Biological activity, soil moisture and Cu have different effects on HCB and DDT transfer from FA, HA and BHA to lipid and IR fractions. AbstractTemporal changes in the distribution of exogenous HCB and DDT among different soil organic matter fractions were studied under sterile and non-sterile conditions, different soil water contents, and different concentrations of added Cu 2þ . The residence time was 311 days. Soil organic matter was fractionated into fulvic acid (FA), humic acid (HA), bound-humic acid (BHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…This is consistent with our earlier findings that the volatility of OCPs and PCBs in sterilized soil did not experience any change over 550 days . Some studies have shown that microbes accelerate the formation of bound residues, while others have suggested that they are capable of releasing the bound residues from soil. , Lack of aging effect in the controls could also be due to an artifact of the gamma-irradiation process which may alter the structure of the soil organic matter, and thus change the sorption behavior of a sterilized soil . It is noted that K SA of the sterile control soils is higher than the nonsterile soil and the reason is unclear.…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with our earlier findings that the volatility of OCPs and PCBs in sterilized soil did not experience any change over 550 days . Some studies have shown that microbes accelerate the formation of bound residues, while others have suggested that they are capable of releasing the bound residues from soil. , Lack of aging effect in the controls could also be due to an artifact of the gamma-irradiation process which may alter the structure of the soil organic matter, and thus change the sorption behavior of a sterilized soil . It is noted that K SA of the sterile control soils is higher than the nonsterile soil and the reason is unclear.…”
Section: Resultssupporting
confidence: 90%
“…The K SA and HPCD% of the Sterile soils generally showed no trend with aging time, with exceptions noted above. Studies on sorption of organic chemicals in sterile vs nonsterile soils have shown that microbes may accelerate the formation of bound residues , . However, MacLeod and Semple reported that there were less pyrene extracted by butanol from soils that had been sterilized.…”
Section: Resultsmentioning
confidence: 99%